Impact of English Proficiency on Academic Performance of International Students - Martirosyan, Nara M.; Hwang, Eunjin; Wanjohi, Reubenson (Journal of International Students, 2015)
Using an ex-post facto, non-experimental approach, this research examined the impact of English language proficiency and multilingualism on the academic performance of international students enrolled in a four-year university located in north central Louisiana in the United States. Data were collected through a self-reported questionnaire from 59 students who were in their sophomore, junior or senior year of college. Statistical analyses revealed significant differences in language proficiency and multilingualism in relation to academic performance. The highest mean GPA was evident among students who had reported high levels of self-perceived English language proficiency, and among students who spoke at least three languages.